Guidelines for Improving Information Leadership of Rural Primary Schools Principals in Guangxi - Zhai Shujuan,; Patchara Dechhome,; Niran Sutheeniran,; Sarayuth Sethakhajorn, (Utilitas Mathematica, 2025)
The objectives of this research were: 1) to study the current situation, 2) to formulate guidelines, and 3)to evaluate suitability and feasibility of guidelines of improving information leadership of Rural Primary Schools Principals in Guangxi . The sample group of this research included 484 Teachers or Vice Principals/ Principals from 241 Primary Schools in Guangxi. Research instruments included: 1) questionnaire, 2) structured interview, and 3) evaluation form. The data were analyzed by percentage, average value, standard deviation, and content analysis. The research results show that: 1) The current situation of information leadership of rural primary schools principals in Guangxi in five aspects was at high level. Considering the results of this research aspects ranged from the highest to lowest mean were as follows: the highest mean was information literacy), followed by Information environment and resource construction ability, Information evaluate ability was the lowest mean. 2) Guidelines for improving information leadership of rural primary schools principals in Guangxi included five aspects with a total 48 measures. There are: 1) Information literacy included 10 measures, 2) Information management ability 10 measures, 3) Information environment and resource construction ability included 8 measures, and 4) Information planning and design ability included 10 measures, 5) Information evaluate ability included 10 measures. The suitability and feasibility evaluation results of guidelines were at high level.